Mapping Global Research on Sustainable Textile Materials: A Comparative Bibliometric Study of China and International Literature (Journal of Fiber Bioengineering and Informatics, 2026)
At present, the world is facing a critical stage of sustainable development transformation. In particular, the introduction of the EU Sustainable Products Regulation (ESPR) marks a fundamental shift in the regulatory paradigm from end-of-pipe governance to ecological design. However, sustainable materials still face challenges in terms of cost, performance, strength, comfort, and large-scale production. At present, there is a lack of cross-country comparative bibliometric analysis on the emerging sustainability trends in textile materials research. Based on this, this study uses CiteSpace (v6.4.RI) to conduct a visual analysis of this field based on Chinese and English literature from 2010 to 2025 in CNKI and Web of Science databases using bibliometric methods. The key analysis indicators include annual publication volume, national and institutional cooperation networks, high-frequency keywords, keyword clustering, evolution path and emerging terms to compare the research status at home and abroad. This study aims to systematically map and compare the domestic and international research trends of sustainable textile materials to determine the evolving themes and future directions. The results show that the number of related papers has continued to grow in the past 14 years, and China is in a leading position in terms of the number of published papers. International cooperation is characterized by multi-center and decentralization. The current research mainly focuses on three directions: material innovation, performance optimization and environmental governance mechanism. It is expected that future research will focus more on bio-based textile technology (especially bionic materials) and intelligent response materials that can be applied on a large scale, such as thermochromic fibers and self-healing composites.
Keywords: Sustainable textile materials; CiteSpace; Knowledge Graph; Visual Analysis; Research Hotspot